Design of Interactive PowerPoint Media on CTL Model in Primary School - Maharani, Siti Dewi; Safitri, Mazda Leva Okta; Setiawan, Fatoni Agus (Universitas Pendidikan Ganesha, 2023)
One of the teacher's tasks is to find ways for students to understand the concept of the lesson without experiencing difficulties. This study aims to produce interactive hyperlink PowerPoint media based on contextual learning models that are feasible to use and to determine their effectiveness. This type of research is Research and Development (R&D) with a 3D+I model (Define, Design, Develop, and Implementation). They collect data in this study using walkthroughs, interviews, and questionnaires. This study involves the assessment of material, media, and design experts. Data analysis techniques using qualitative and quantitative descriptive analysis. The media expert validation assessment results were categorized as